Importance of evaluation, co-evaluation and self-assessment in university education: Experiences in Art Education - Moreno Pabón, Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Studies carried out on university evaluation, show how emotional stress increases during exam periods and grades. In an integral learning, the evaluation cannot depend on the note of an exam. The new teaching and learning methodologies seek a collaborative approach between teacher and student, with a common goal: the comprehensive evaluation of the student body. The objectives of this work are to verify if another type of evaluation, more dynamic and democratic, is possible. ¿Will continuous assessment, self-assessment, coevaluation or heteroevaluation together with gamification, avoid confrontations, stressful situations and distancing between teacher and student?